The activity of BcsZ of Salmonella Typhimurium and its role in Salmonella-plants interactions - Fratty, Ilana S.; Shachar, Dina; Katsman, Marina; Yaron, Sima (Frontiers in Cellular and Infection Microbiology, 2022)
Salmonella enterica is one of the most common human pathogens associated with fresh produce outbreaks. The present study suggests that expression of BcsZ, one of the proteins in the bcs complex, enhances the survival of Salmonella Typhimurium on parsley. BcsZ demonstrated glucanase activity with the substrates carboxymethylcellulose and crystalline cellulose, and was responsible for a major part of the S. Typhimurium CMCase activity. Moreover, there was constitutive expression of BcsZ, which was also manifested after exposure to plant polysaccharides and parsley-leaf extract. In an in-planta model, overexpression of BcsZ significantly improved the epiphytic and endophytic survival of S. Typhimurium on/in parsley leaves compared with the wild-type strain and bcsZ null mutant. Interestingly, necrotic lesions appeared on the parsley leaf after infiltration of Salmonella overexpressing BcsZ, while infiltration of the wild-type S. Typhimurium did not cause any visible symptoms. Infiltration of purified BcsZ enzyme, or its degradation products also caused symptoms on parsley leaves. We suggest that the BcsZ degradation products trigger the plant’s defense response, causing local necrotic symptoms. These results indicate that BcsZ plays an important role in the Salmonella-plant interactions, and imply that injured bacteria may take part in these interactions.